More answers

y = x + 1 and y = - x - 5

so x + 1 = - x - 5 so that 2x = -6 and x = - 3

Finally, y = x + 1 = - 3 + 1 = - 2

Q: What is y equals x plus 1 and y equals -x-5?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

1,565 = x5 1,5651/5 = (x5)1/5 1,5651/5 = x5/5 1,5651/5 = x 4.3541 = x

5+5x5=30 but (5+5)x5=50

1

0 because X= -1

7=x+1 6=x

Related questions

1,565 = x5 1,5651/5 = (x5)1/5 1,5651/5 = x5/5 1,5651/5 = x 4.3541 = x

5+5x5=30 but (5+5)x5=50

x10 = x5.x5 = (x5)2 [x power five whole squared] Equation is x10 + x5 - 2 Replacing x10 (x5)2+x5 - 2 Substituting x5 by Y Equation becomes Y2 + Y - 2 = 0 Y2 + 2Y - Y - 2 = 0 Y(Y + 2) - 1(Y+2) = 0 (Y-1)(Y+2) = 0 The values of Y are 1 and -2 Y = x5 = 1 Therefore, x = 1 Y = x5 = -2 x = fifth root of -2, which is an imaginary value.

1

0 because X= -1

7=x+1 6=x

Since x and y are variables, the sum of 5x and 5y could be literally any number.

The answer to the problem of 12X plus 13 equals 9 is x equals -1/3.

x = 0

1+x=dd+x so dd=1 so d=1 1+x=89b+x so 89b=1 so b=1/89 bc+x=1+x so bc=1 so c=1/(1/89) = 89 so cd=89 (and x=88)

(1, 9)

5